Dari Brosur Ke Tiktok Live: Kajian Literatur Transformasi Strategi Marketing Umkm di Era Digital - Rania Cundamanik Wisand; Arthanami Nauli Panggabean; Rahma Sugihartati; Dessy Harisanty; Dina Septiani (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
Digital transformation has driven significant changes in marketing strategies adopted by micro, small, and medium enterprises (MSMEs), particularly among businesses that previously relied on brochures, WhatsApp messages, or word-of-mouth communication to inform consumers about selling locations and schedules. Recent phenomena indicate that MSMEs have begun to shift their approach by utilizing TikTok Live to conduct mobile selling activities in real time, showcase the selling process, and provide up-to-date location information to consumers. This transformation is not merely technological in nature, but is also closely related to human resource capabilities in managing content, building interaction, and utilizing digital features as part of marketing strategies. This study aims to review how the transformation of MSME marketing strategies occurs in the digital era by emphasizing the role of human resource competencies in the utilization of TikTok Live. The study employs a Literature Review (LR) method by analyzing various studies on digital marketing, consumer behavior, live streaming, and human resource capacity development in MSMEs. The findings indicate that TikTok Live offers opportunities for MSMEs to expand market reach, present products directly to consumers, and build interactive relationships with audiences. The effectiveness of its utilization is strongly influenced by human resource capabilities in operating technology, creating engaging content, and communicating persuasively in digital spaces. These findings highlight that digital marketing transformation depends not only on the platform used, but also on the quality of human competencies managing it. This study contributes to the development of MSME marketing strategies and serves as a reference for business practitioners, policymakers, and academics in strengthening human resource capacity in the digital era.